PENINGKATAN HASIL BELAJAR SISWA KELAS VC SDN 01 TAMAN MELALUI MODEL TEAM GAMES TOURNAMENT - Meyren, Sukma Dwi; Tryanasari, Dewi; Jatmikawati, Melina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is a collaborative classroom action research conducted with class 5C teachers at SDN 01 Taman to determine the effectiveness of the game method in improving student learning outcomes in thematic learning. The research was carried out at SDN 01 Taman Madiun from February to April 2024 in the 2023/2024 academic year. The subjects of this research were 28 students in class V-C at SDN 01 Taman. This research consists of pre-cycle, cycle I and cycle II stages. Each of the two research process cycles has three stages, namely: planning, research implementation, observation, and reflection. The data analysis technique is to compare student learning outcomes before and after the actions in Cycle I and Cycle II. The research results show that the game method can improve student learning outcomes. This is proven by the increase in learning outcomes observed in both cycle 1 and cycle 2. In the pre-cycle the average value was 62.3, then in cycle 1 there was an increase, namely 71.1, while in cycle 2 there was a quite significant increase, namely 80,9.